Chloroplast Genome Sequencing, Comparative Analysis, and Discovery of Unique Cytoplasmic Variants in Pomegranate (Punica granatum L.) - Nripendra Vikram Singh; Prakash Goudappa Patil; Roopa P. Sowjanya; Shilpa Parashuram; Purushothaman Natarajan; Karuppannan Dhinesh Babu; Ram Krishna Pal; Jyotsana Sharma; Umesh K. Reddy (Frontiers in Genetics, 2021)
Here we report on comprehensive chloroplast (cp) genome analysis of 16 pomegranate (Punica granatum L.) genotypes representing commercial cultivars, ornamental and wild types, through large-scale sequencing and assembling using next-generation sequencing (NGS) technology. Comparative genome analysis revealed that the size of cp genomes varied from 158,593 bp (in wild, “1201” and “1181”) to 158,662 bp (cultivar, “Gul-e-Shah Red”) among the genotypes, with characteristic quadripartite structures separated by a pair of inverted repeats (IRs). The higher conservation for the total number of coding and non-coding genes (rRNA and tRNA) and their sizes, and IRs (IR-A and IR-B) were observed across all the cp genomes. Interestingly, high variations were observed in sizes of large single copy (LSC, 88,976 to 89,044 bp) and small single copy (SSC, 18,682 to 18,684 bp) regions. Although, the structural organization of newly assembled cp genomes were comparable to that of previously reported cp genomes of pomegranate (“Helow,” “Tunisia,” and “Bhagawa”), the striking differences were observed with the Lagerstroemia lines, viz., Lagerstroemia intermedia (NC_0346620) and Lagerstroemia speciosa (NC_031414), which clearly confirmed previous findings. Furthermore, phylogenetic analysis also revealed that members outside the genus Punica were clubbed into a separate clade. The contraction and expansion analysis revealed that the structural variations in IRs, LSC, and SSC have significantly accounted for the evolution of cp genomes of Punica and L. intermedia over the periods. Microsatellite survey across cp genomes resulted in the identification of a total of 233 to 234 SSRs, with majority of them being mono- (A/T or C/G, 164–165 numbers), followed by di- (AT/AT or AG/CT, 54), tri- (6), tetra- (8), and pentanucleotides (1). Furthermore, the comparative structural variant analyses across cp genomes resulted in the identification of many varietal specific SNP/indel markers. In summary, our study has offered a successful development of large-scale cp genomics resources to leverage future genetic, taxonomical, and phylogenetic studies in pomegranate.